Factors Affecting the Welfare of Labors in Indonesia - Rohayani ROHAYANI; Ghozali MASKIE; Moh. KHUSAINI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The national development goals of Indonesia were explicitly stated in the 1945 constitution, one of the goals was to increase public welfare and educate the life of the nation. In line with the goals in the points of Sustainable Development Goals (SDGs). Development in Indonesia that has been carried out through measures of poverty, unemployment, and inequality has not been successful. Therefore, the development paradigm began to change to the human capital in a country. If human capital development is carried out, it can induce an increase in welfare through other aspects, such as the use of technology and an increased in labor productivity. In addition to human capital, this study also measured the influence of regional factors, which are often related to infrastructure built with the aim of increasing economic activity. This study aims to analyze the factors that affect the welfare in Indonesia using a quantitative approach with a logistic regression method. The result showed that education, health, and some control variables such as age and the number of dependents had a significant effect on welfare in a =1% and all independent variables used in this study simultaneously had a significant effect on welfare.